2021
DOI: 10.1093/eurpub/ckaa254
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of user fee for language interpretation: effects on use of interpreters in Danish health care

Abstract: Amendments to the Danish Health Act were introduced in 2018 that stated immigrant patients who have resided in Denmark for more than 3 years have to pay user fees for interpretation in health care. The aim of the study was to explore, how the use of interpreters was affected by the introduction of user fees for interpretation. Results showed a considerable decrease in interpretation services following the introduction of the fee. It is likely to assume that the reduced utilization of interpretation services is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This finding is in line with other studies that show how fees for interpreting services, as well as for preventive health care and curative services, might lead to a decline in the use of (not the need for) such services [Ministerie van Volksgezondheid Welzijn en Sport (Ministry of Public Health Well-being and Sports), 2013; De Boe, 2015; Michaëlis, Krasnik and Norredam, 2021] and ultimately to a lower use of necessary health-care services (Danish Medical Association and The Danish Institute for Human Rights, 2019) as well as lower compliance (Van Wieringen, et al , 2002). In this way, user fees create not only a structural barrier to accessing professional interpreting services but also a barrier to access and use health-care services for many minority-language patients (Flores, 2005; Iliadi, 2008; Donnelly et al , 2011; Ohtani et al , 2015; Gil-Gonzalez et al , 2015; O’Donnell et al , 2016; Floyd and Sakellariou, 2017; Mangrio and Sjögren Forss, 2017; Czapka, Gerwing and Sagbakken, 2019; de Moissac and Bowen, 2019; Al Shamsi et al , 2020; Rasi, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in line with other studies that show how fees for interpreting services, as well as for preventive health care and curative services, might lead to a decline in the use of (not the need for) such services [Ministerie van Volksgezondheid Welzijn en Sport (Ministry of Public Health Well-being and Sports), 2013; De Boe, 2015; Michaëlis, Krasnik and Norredam, 2021] and ultimately to a lower use of necessary health-care services (Danish Medical Association and The Danish Institute for Human Rights, 2019) as well as lower compliance (Van Wieringen, et al , 2002). In this way, user fees create not only a structural barrier to accessing professional interpreting services but also a barrier to access and use health-care services for many minority-language patients (Flores, 2005; Iliadi, 2008; Donnelly et al , 2011; Ohtani et al , 2015; Gil-Gonzalez et al , 2015; O’Donnell et al , 2016; Floyd and Sakellariou, 2017; Mangrio and Sjögren Forss, 2017; Czapka, Gerwing and Sagbakken, 2019; de Moissac and Bowen, 2019; Al Shamsi et al , 2020; Rasi, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…However, studies have also shown that a decline in the utilization of interpreting services can be observed following the introduction of user fees for such services [Ministerie van Volksgezondheid Welzijn en Sport (Ministry of Public Health Well-being and Sports), 2013; De Boe, 2015; Danish Medical Association and The Danish Institute for Human Rights, 2019; Michaëlis, Krasnik and Norredam, 2021]. This is in line with our findings and suggests that the fee creates an additional practical barrier to accessing the necessary assistance in the recommended and preferred form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with mental or physical diseases can be exempted from the co-payment. Previously, interpretation was without user payments, and after the amendments, the use of interpreter services dropped (38).…”
Section: Study Setting: Antenatal Care In Denmarkmentioning
confidence: 99%
“…It was shown prior to implementation of the current law that the use of professional interpreters in Danish health care was lacking and with possible impact on quality of care ( Lund Hansen MT 2013 ). A recent review showed a decrease in use of interpreters since implementation of the law in 2018 ( Michaëlis et al., 2021 ), possibly reducing quality of care for patients in need of interpreter service even further.…”
Section: Introductionmentioning
confidence: 99%